Microscopic Residual Tumor After Pancreaticoduodenectomy: Is Standardization of Pathological Examination Worthwhile?. Issue 5 (May 2016) - Borzomati, Domenico; Perrone, Giuseppe; Nappo, Gennaro; Valeri, Sergio; Amato, Michela; Petitti, Tommasangelo; Muda, Andrea Onetti; Coppola, Roberto
Abstract : Objectives: R1 resection rate after pancreaticoduodenectomy (PD) for cancer is highly variable. The aim of this study was to verify if a standardized histopathological work-up of the specimen affects the rate of R1 resection after PD for cancer. Methods: Two groups of specimens were managed with (standardized method [SM] group) or without (non-standardized method [NSM] group) a SM of histopathological work-up. Each group included 50 cases of PD for periampullary cancer. Differences in terms of R1 resection rate between the 2 groups were evaluated. Correlation between R1 status and local recurrence was also evaluated. Results: The cohort of 100 patients consisted of 66 pancreatic ductal adenocarcinoma, 15 cholangiocarcinoma, and 19 ampullary cancer. The R1 resection rate resulted statistically higher in the SM group (66% vs 10%). Local recurrence was more frequently related to R1 resection in the SM group (34.3% of cases) than in NSM group (20% of cases). Conclusions: The use of the SM of pathological evaluation of the specimen after PD for cancer determines a significant increase of R1 resection. This remarkable difference seems to be due to the different definition of minimum clearance. The SM seems to better discriminate patients in terms of risk of local recurrence.